(untitled) (Laisvalaikio tyrimai, 2022)
Relevance and novelty. The relevance of the study of the topic is that the problem of national security is a problem that seriously worries public and state figures, scientists and ordinary citizens. This is due to traditional threats - war, political instability, natural disasters, as well as the emergence at the beginning of the XX-XXI century of a large number of qualitatively new threats to national security, directly related to the life of the country and the population. All this, in turn, necessitates the search for a new security paradigm in the interests of the survival of all mankind. The processes of globalization have increased the interdependence of nature and society, man and society, which means scientific understanding, comprehensive analysis and development of theoretical views that can adequately reflect in scientific categories the ideas about modern processes on which national security depends. The purpose of the study is to consider the theoretical and methodological aspects of the state policy of national security. Research objectives: to conduct a theoretical and conceptual analysis of the security phenomenon; explore the conceptual and categorical apparatus of national security. Methodology. The study is based on the principles of dialectics, objectivity, historicism, which made it possible to carefully comprehend the object of study, take into account the multidimensionality of problems in the field of security policy, avoid tendentiousness and bias, reveal the evolution of security policy as a complex and controversial political process. The system method was used in the interpretation of security policy as an integral element of the policy of the state and citizen. The historical method made it possible to track the evolution of scientific approaches to understanding the relationship between security and the concept of a welfare state. The dialectical method made it possible to reveal contradictions between the interests of the state in relation to national security and the interests of individuals in ensuring security. The scientific novelty of the results obtained is based on the substantiation of a new approach to understanding security policy and the conceptualization of its features and role in the modern world. The value of the study is based on the study of the features of state policy in the field of national security. Outcomes and conclusions. Having carried out a theoretical and conceptual analysis of the phenomenon of security, we note that security can be considered as the protection of such areas of the individual, family, nation and humanity: objectively spiritual being - spiritual life in their sociality: spiritual values, faith, morality, identity, culture, mentality; material-subject being - the material conditions of existence, provided through the activity of creating the necessary objects, primarily in the labor, economic, household spheres of being; socio-historical being - these are real social and international relations in historical time and in a certain geopolitical space, the preservation, development and transformation of existing states, countries, civilizations; subjective-personal being - and the diversity that occurs only with them, and which thereby differ from the general course of life. What swings national security is the state of protection of the vital interests of the individual, society and the state from internal and external threats, the ability of the state to maintain its sovereignty and territorial integrity and act as a subject of international law. Key words: national security, politics, government, hybrid warfare, geopolitics